Digital Environment for Movement Control in Surgical Skill Training. - Juanes, Juan; Gómez, Juan; Peguero, Pedro; Ruisoto, Pablo (Journal of Medical Systems, 2016)
Intelligent environments are increasingly becoming useful scenarios for handling computers. Technological devices are practical tools for learning and acquiring clinical skills as part of the medical training process. Within the framework of the advanced user interface, we present a technological application using Leap Motion, to enhance interaction with the user in the process of a laparoscopic surgical intervention and integrate the navigation through augmented reality images using manual gestures. Thus, we intend to achieve a more natural interaction with the objects that participate in a surgical intervention, which are augmented and related to the user's hand movements.